Penegakan Hukum dalam Penanggulangan Pertambangan Batubara Illegal - Trias Nugraha (Savana, 2024)
Coal mining is one sector that supports state and regional economies if management is environmentally friendly. Management of coal mining as a non-renewable natural resource must be carried out as optimally as possible, efficiently, transparently, sustainably and with environmental awareness. The aim of the research is to find out and analyze the regulation and law enforcement against illegal mining in Indonesia. The research method used by the author in researching the problem in writing this article is normative juridical research. The results of the research are the regulation of Article 158 of Law Number 4 of 2009 concerning Mineral and Coal Mining where if someone does not have an IUP, IPR, IUPK then they will be imprisoned for a maximum of 10 years and a maximum fine of IDR 10,000,000,000.00 (ten billion)  Enforcement The law in illegal mining cases is the decision of the Panel of Judges to sentence the Defendant to imprisonment for 8 (eight) months and a fine of IDR. 2,000,000.00 (two million Rupiah). The conclusion is that the mining issue cannot be separated from the agrarian issue, because Mining activities are underground and to carry out these activities, you must first obtain permission from the authorized official. Therefore, when carrying out mining activities, you must have a permit as regulated in the Coal Mining Licensing Regulations, Law Number 4 of 2009 concerning Mineral Mining. and Coal which discusses the form of regulatory licensing and licensing requirements.